2021
DOI: 10.1080/17437199.2021.1962386
|View full text |Cite
|
Sign up to set email alerts
|

The effect of choice interventions on retention-related, behavioural and mood outcomes: a systematic review with meta-analysis

Abstract: The provision of choice within interventions has been associated with increased motivation, engagement and interest, as well as improved clinical outcomes. Existing reviews are limited by their wide inclusion criteria or by not assessing behaviour change and mood outcomes. This review examines whether participant-driven choice-based interventions specifically are more likely to be enjoyed and accepted by participants compared to no-choice interventions, and whether this impacts on intervention outcomes in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…It is noteworthy that others have similarly reported that when given a choice of positive mood interventions, self-selection is no more effective than random assignment (Silberman, 2007). Indeed, in a recent systematic review and meta-analysis comparing choice-based interventions to matched nonchoice interventions (across a range of contexts) the authors found that while providing participants choice reduced attrition and increased satisfaction with the intervention, there was only weak (nonsignificant evidence) that this influenced mood-related outcomes (Carlisle et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that others have similarly reported that when given a choice of positive mood interventions, self-selection is no more effective than random assignment (Silberman, 2007). Indeed, in a recent systematic review and meta-analysis comparing choice-based interventions to matched nonchoice interventions (across a range of contexts) the authors found that while providing participants choice reduced attrition and increased satisfaction with the intervention, there was only weak (nonsignificant evidence) that this influenced mood-related outcomes (Carlisle et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This might include study designs that allow participants their choice of intervention. Choice-based interventions have been shown improve participant retention, adherence, satisfaction and behaviour change 39. Of individuals assessed for eligibility, 61% declined to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Choice-based interventions have been shown improve participant retention, adherence, satisfaction and behaviour change. [39] Of individuals assessed for eligibility 61% declined to participate. The underlying reasons for declining participation in this trial are unable to be elucidated, however in other respiratory populations undertaking exercise/activity related studies, a preference for receiving a specific treatment arm is commonly cited.…”
Section: Future Research Considerationsmentioning
confidence: 99%
“…Bad effects: the proportion of participants who reported experiencing bad effects or lasting bad effects from the intervention (as described in the study by Carlisle et al [ 35 ]) and the proportion of participants whose PHQ-8 scores increased above the minimally clinically important difference for the PHQ-8 (≥5 points [ 46 ]), assessed at t 1 and t 2…”
Section: Methodsmentioning
confidence: 99%
“…The Unmind app deliberately includes interventions that use different therapeutic modalities, giving the user free choice over which modality feels the most relevant and appealing to them. This is important, as a recent meta-analysis suggests that giving users autonomy and choice over intervention parameters leads to greater adherence and better clinical outcomes [ 35 ]. Thus, this study aimed to evaluate the feasibility and acceptability of the 3 interventions independently (using an efficient multiarm design) without directly comparing them.…”
Section: Introductionmentioning
confidence: 99%